Sequential decisions in the Diamond-Dybvig banking model - Markus Kinateder; Hubert János Kiss (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
We study the Diamond-Dybvig model of financial intermediation (JPE, 1983) under the assumption that depositors have information about previous decisions. Depositors decide sequentially whether to withdraw their funds or continue holding them in the bank. If depositors observe the history of all previous decisions, we show that there are no bank runs in equilibrium independently of whether the realized type vector selected by nature is of perfect or imperfect information.
Keywords: C72; D82; G21; 330; Bank Run; Imperfect Information; Perfect Bayesian Equilibrium